Polyembryony and identification of Volkamerian lemon zygotic and nucellar seedlings using RAPD - Andrade-Rodríguez, María; Villegas-Monter, Angel; Carrillo-Castañeda, Guillermo; García-Velázquez, Armando (Pesquisa Agropecuaria Brasileira, 2004)
The objectives of this work were to evaluate the frequency of polyembryony, and to identify zygotic and nucellar seedlings of Citrus volkameriana using RAPD. Twenty-five polyembryonic and eight monoembryonic seeds were cultivated in vitro for six months. DNA from seedlings was extracted and used in combination with five RAPD primers to identify zygotic or nucellar origin of the seedlings. Environmental conditions of the year affected significantly (P≤0.05) the morphological characteristics of fruits and the number of embryos per seed. Polyembryonic seeds ranged from 30.9%, 44.8% to 54.4% over three years. Morphological characteristic was not correlated with polyembryony. In vitro culture enable all embryos of each seed to grow, favoring the percentage of seedlings identified as zygotic. In polyembryonic and monoembryonic seeds, 25.9% and 87.5% of the seedlings, respectively, were sexually originated. In polyembryonic seeds, not all zygotic seedlings were produced by small embryos located at the micropyle.